Barramento de serviços federados para integração federativa de sistemas distribuídos - Camelo, Josênio Candido (2008)
This work presents the Federated Service Bus (FSB), a communication middleware based on Enterprise Service Bus (ESB) for federated systems. We do not address the classic problem of federated systems, focused mainly on authentication and security, but a growing need for heterogeneous service intercommunication. The proposed middleware makes use of internal ESBs to allow the isolation, application of policies and routing of each domain that comprises the federal system, seeking separate interests and avoid conflicts. Our proposal is modeled using coloured Petri nets, which gives it reliability of simulation and validation based on a formal mathematical model. Thus, significant gains were achieved in the implementation with the use of web services and BPEL (Business Process Execution Language). The modeling with coloured Petri nets not only validated the flow as allowed a error reduction. Finally, the FSB is embedded with SOA (Service Oriented Achitecture), EDA (Event-Driven Architecture) and NGOSS (Next Generation Operation System and Software).